Three-in-one to enhance visible-light driven photocatalytic activity of BiOCl: Synergistic effect of mesocrystalline stacking superstructure, porous nanosheet and oxygen vacancy - Xianzi Li; Shaodong Sun; Xin Zhang; Xiaochuan Zhang; Jie Cui; Qing Yang; Shuhua Liang (Journal of Materiomics, 2021)
Simultaneously integrating mesocrystalline stacking superstructures, porous nanosheets and defective oxygen vacancies (OVs) into BiOCl crystals is an available strategy to enhance the visible-light-driven photocatalytic activity. Herein, we report a facile etching agent-assisted hydrothermal approach to achieve one-pot fabrication of mesocrystalline BiOCl porous nanosheet stacking superstructures with defective OVs, which show high catalytic activities towards to the visible-light-driven degradation of organic dyes. The formation of stacking superstructure in a mesocrystalline BiOCl is responsibility for increasing the transport of charge carriers. Experimental results and theoretical calculations suggest that the presence of OVs is beneficial to tuning the energy band structure for the improvement of visible light harvesting, prolonging the lifetime and enhancing the oxidation activity of photogenerated charge carriers. Additionally, the porous morphology and thin nanosheet building block could supply abundant active sites for photocatalysis. This research might arouse in-depth investigations on the development of novel precursor-modified strategy for the synthesis of high-active BiOX (X = Cl, Br and I)-based photocatalysts.